Impersonal Care or Humanized Care : a Decision Made by Nurses? Hourglass Model (2016)
ABSTRACT: This work sought to understand the meaning of the experience of caring and how patients, family members, and nurses describe it. Methods. This was a phenomenological interpretive study with 16 adult participants between 29 and 62 years of age, selected through purposeful sampling. The study was based on in-depth interviews to construct the information and on the procedures proposed by Munhal for the analysis. Results. This work revealed a complex relation, understood as vicariant, between humanized care and impersonal care that influence upon independent aspects of the social and legal system, health institutions, and nurses. The themes comprising the experience of humanized care are described in the “hourglass” model. Conclusion. Humanized care can displace impersonal care or vice versa, according to the orientation of nurses in the care practice and some elements from the institutional context.